Alpha/Beta-Hydrolase Domain-Containing 6: Signaling and Function in the Central Nervous System - Zhang, Haofuzi; Li, Xin; Liao, Dan; Luo, Peng; Jiang, Xiaofan (Frontiers in Pharmacology, 2021)
The endocannabinoid (eCB) signaling system plays an important role in the regulation of the central nervous system (CNS). α/β-Hydrolase domain-containing 6 (ABHD6) is a transmembrane serine hydrolase that can hydrolyze monoacylglycerol (MAG) lipids such as endocannabinoid 2-arachidonic acid glycerol (2-AG); participate in neurotransmission, inflammation, glucose and lipid metabolism, tumorigenesis and other biological processes; and be a potential therapeutic target for various neurological diseases, such as traumatic brain injury (TBI), multiple sclerosis (MS), epilepsy, mental illness and pain. This review summarizes the molecular mechanisms of action and biological functions of ABHD6, particularly its mechanism of action in the pathogenesis of neurological diseases, and provides a theoretical basis for finding new pharmacological intervention targets by targeting ABHD6.